Phosphoproteomic analysis identifies phospho-Threonine-17 site of phospholamban important in low molecular weight isoform of fibroblast growth factor 2-induced protection against post-ischemic cardiac dysfunction. (November 2020) - Manning, Janet R.; Wijeratne, Aruna B.; Oloizia, Brian B.; Zhang, Yu; Greis, Kenneth D.; Schultz, Jo El J.
Abstract: Rationale: Among its many biological roles, fibroblast growth factor 2 (FGF2) protects the heart from dysfunction and damage associated with an ischemic attack. Our laboratory demonstrated that its protection against myocardial dysfunction occurs by the low molecular weight (LMW) isoform of FGF2, while the high molecular weight (HMW) isoforms are associated with a worsening in post-ischemic recovery of cardiac function. LMW FGF2-mediated cardioprotection is facilitated by activation of multiple kinases, including PKCalpha, PKCepsilon, and ERK, and inhibition of p38 and JNK. Objective: Yet, the substrates of those kinases associated with LMW FGF2-induced cardioprotection against myocardial dysfunction remain to be elucidated. Methods and results: To identify substrates in LMW FGF2 improvement of post-ischemic cardiac function, mouse hearts expressing only LMW FGF2 were subjected to ischemia-reperfusion (I/R) injury and analyzed by a mass spectrometry (MS)-based quantitative phosphoproteomic strategy. MS analysis identified 50 phosphorylation sites from 7 sarcoendoplasmic reticulum (SR) proteins that were significantly altered in I/R-treated hearts only expressing LMW FGF2 compared to those hearts lacking FGF2. One of those phosphorylated SR proteins identified was phospholamban (PLB), which exhibited rapid, increased phosphorylation at Threonine-17 (Thr17) after I/R in hearts expressing only LMW FGF2; this was further validated using Selected Reaction Monitoring-based MS workflow. To demonstrate a mechanistic role of phospho-Thr17 PLB in LMW FGF2-mediated cardioprotection, hearts only expressing LMW FGF2 and those expressing only LMW FGF2 with a mutant PLB lacking phosphorylatable Thr17 (Thr17Ala PLB) were subjected to I/R. Hearts only expressing LMW FGF2 showed significantly improved recovery of cardiac function following I/R ( p < 0.05), and this functional improvement was significantly abrogated in hearts expressing LMW FGF2 and Thr17Ala PLB ( p < 0.05). Conclusion: The findings indicate that LMW FGF2 modulates intracellular calcium handling/cycling via regulatory changes in SR proteins essential for recovery from I/R injury, and thereby protects the heart from post-ischemic cardiac dysfunction. Graphical abstract: Unlabelled Image Highlights: LMW FGF2 improves post-ischemic recovery of cardiac function. Phosphoproteomic/SRM mode identified SR proteins in LMW FGF2 cardioprotection. Threonine-17 site of PLB important for LMW FGF2 effect against ischemic dysfunction. LMW FGF2 improves post-ischemic recovery via multiple calcium handling proteins/genes.